The Antioxidant Effect of Nanoparticle Gels Grounds Arabica Coffee (Coffea arabica L.) - Salfauqi Nurman; Ruka Yulia; Irmayanti Irmayanti; Erliza Noor; Titi Candra Sunarti (International Conference on Multidisciplinary Research, 2021)
Arabica coffee’s grounds are the wastes from the production of coffee beverages and are known to contain several active compounds that can be used as an antioxidant. This research is therefore a follow-up work on the use of these coffee grounds nanoparticles as an active compound in gel production. This study focuses on the antioxidant effects of the gel product, using Box-Behnken Design with 3 factors(x) (carbopol 940, TEA, and coffee grounds nanoparticles) at 3 levels. Based on the results of this study, it is found that the high antioxidant effect with an average inhibition value was 43.485%.Furthermore, data analysis on the other hand showed a significant effect of linear Box-Behnken Design model on percentage inhibition with a p-value greater than 0.0001 and insignificant lack of fit validated by an F-value of 0.60, in addition to a p-value of 0.7621. The optimal solution of about 0.50% carbopol, 940 formulation, 0.40% TAE, and 2,313% nanoparticles produced 45,636% inhibition value with 0.812 desirability. Moreover, this arabica coffee grounds can be claimed as a new invention that has great potential in the health sector as an active compound for pharmaceutical preparations.Keywords: Inhibition, Nanogel, Coffee Grounds, Box-behnken